Provider & nursing perspectives on the "panculture": opportunities for innovative diagnostic stewardship interventions - Kevin M. Gibas; Leonard A. Mermel (Cambridge University Press, 2024)
Abstract Objective: To examine practices of providers and nursing staff in evaluating febrile patients and identify drivers of excessive diagnostic testing. Design: Prospective multiple-choice surveys. Setting: Inpatient areas and the Emergency Department at Rhode Island Hospital (RIH) in Providence, RI. Participants & Methods: We conducted two surveys focused on the evaluation of febrile inpatients at RIH. One survey was of providers trained in internal medicine, surgery, pediatrics, emergency medicine, and neurology; the other survey was of nursing staff (registered nurses and certified nursing assistants), in inpatient areas and the emergency department. Results: 70 providers (9%) and 178 nursing staff (12%) completed the surveys. 64% of providers (n = 43) reported "always" or "often" ordering full fever workups and 67% of providers (n = 47) reported "always" or "often" physically evaluating febrile patients. Nurses were less likely than providers to report that providers "always" or "often" physically evaluate febrile patients (n = 80, 45%; P < 0.01) and more likely to report providers "always" or "often" order full fever workups (n = 135, 76%; P = 0.04). 71% of providers (n = 50) reported "always" or "often" receiving written handoffs. 86% of providers (n = 60) reported handoffs are "always" or "often" accurate; however, only 17% of providers responded these were "always" accurate. 77% of providers (n = 54) reported "always" or "often" following handoff instructions to obtain a full fever workup for febrile patients, regardless of clinical status. Responses differed significantly by unit type and provider specialty and position. Conclusions: This study elucidates drivers of inefficient and excessive utilization of diagnostic studies and identifies targets for diagnostic stewardship interventions.